Pengaruh Core Stability Exercise Terhadap Pengurangan Nyeri Punggung Bawah Myogenic Pada Pengrajin Batik Tradisional PT. Danar Hadi Surakarta - Pratama, Diasnopta; , Totok Budi Santoso , S.Fis , MPH; , Umi Budi Rahayu, S.Fis.,Ftr.,M.Kes (2015)
The working conditions are forcing workers always work on the attitudes and positions that are not natural long-lasting and permanent static that can trigger a variety of complaints on pembatik one of which is Lower Back Pain (LBP). Lower back pain myogenic is lower back pain caused by disorders or musculoskeletal disorders accompanied by neurological disorders between vertebrae thoraces 12 to the bottom of the hip or anus.To determine the effect of the reduction of core stability exercise lower back pain in traditional batik craftsmen PT. Dana Hadi Surakarta. Methods: This study is a Quasi Experimental study with pre-test and post-test with control group design. These samples included 30 respondents. Measuring tools using Visual Analog Scale (VAS). Analysis using Paired Sample T-Test and Independent Sample T-Test.There are differences in the influence of core stability exercises to decrease low back pain myogenic treatment group and the control group.